Ciliwung River Normalization Analysis using HEC-RAS Application (TB. Simatupang Bridge to Bidara Cina) - Imammuddin, Mohammad; Priyo Andi Wicaksono, Dwi (ASTONJADRO, 2023)
Ciliwung River area which starts from TB. Simatupang Bridge to Bidara Cina is one of the areas that experienced severe flooding.This is caused by changes or conversion of land functions which were originally a water catchment area into settlements. Buildings that stand along the river body makes the current cross section of the Ciliwung River unable to function optimally in accommodating flood discharges. In addition, there is no public awareness in protecting the environment, it can be seen from the large piles of garbage on the riverside of the Ciliwung River.One of the efforts made by the government in flood control is river normalization, but in practice the normalization of the Ciliwung River can be said to be not running optimally. The purpose of this research is : the Author want to know how big the capacity of Ciliwung River existing cross section (starting from TB Simatupang Bridge to Bidara Cina) using Hec-Ras software application to modeling the river's cross section existing and so does recording and mapping ofpotentialflood locations. Based on the hydrology calculation, known that flood discharge plan Q25is 404.3m3/s, while the hydraulic Q is only 79.03 m3/s, the Q total is 483,38 m3/s. The results of modeling using the Hec-Ras river cross section existingcannot accommodate the planned flood discharge so that river normalization efforts are needed. Recording and mapping flood locations are useful to get the effectivity of River's normalization according to flood controlling at Ciliwung River (specific at TB Simatupang Bridge to Bidara Cina).